The Study of the Motor coincidence and sensitive- Kinetic Perception and its Relation them with Artistic Performance Level in Gymnastics Skills for Women - Shehab, Zahra (Journal of Physical Education, 2012)
The aim of this study was Identifying the relation of coordination and kinesthetic perception with artistic performance level in gymnastics skills for students in second class from the college of physical education/ university of Baghdad/ Al - jadreia .The searchers have been used the descriptive method in scanning style .The subject of this search has been taken (45) female - student in second class from the college of physical education/ university of Baghdad . The searchers have reached into specific conclusions concerning with statistic analysis about immoral joint relation between sensitive- kinetic coincidence and realization and with Artistic Performance Level in Gymnastics Skills for Women for second class .The an important recommendations by researchers have tackled the necessity of development elements coincidence and realization and with Artistic Performance Level in Gymnastics Skills for Women for second class .